Cognitive Learning Styles Used by Male and Female Students in Grade 10 of Natural Science of “X” School in Surabaya - Febe Widarma (Institute of Research and Community Outreach - Petra Christian University, 2019)
This study identifed male and female’s cognitive learning styles and found out the differences and similarities the cognitive learning styles between male and female students in grade 10 of “X”school in Surabaya. There were twenty six students in Natural Science class (X-IPA1). The main theory for this study is from Ehrman (1996) about Cognitive Learning Styles. The method was mixed-methods. The researcher distributed questionnaires adapted from Ehrman and Leaver (2002b) ind interview to the students in order to know their cognitive learning styles. The findings showed that male students were concrete and female students were analog learners. Additionally, the finding also showed that the male and female students had five similarities and five differences. English teachers will be easier to conduct classroom activites based on the findings of male and female students’ cognitive learning styles. Key words: Cognitive learning styles, learning style, gender